Endovascular treatment of intracranial aneurysms with the Woven EndoBridge device: mid term and long term results. (20th February 2017) - Mine, Benjamin; Goutte, Alexandra; Brisbois, Denis; Lubicz, Boris
Abstract : Purpose: To evaluate the clinical and anatomical results of treatment of intracranial aneurysms (IA) with the Woven EndoBridge (WEB) device, with emphasis on mid term and long term follow-up. Methods: Between November 2010 and November 2015, we retrospectively identified, in our prospectively maintained database, all patients treated by WEB device placement for an IA at three institutions. Clinical charts, procedural data, and angiographic results were reviewed. Results: 48 patients with 49 IAs were identified. There were 35 women and 13 men with a mean age of 57 years (range 35–76 years). All IA were wide necked. Mean aneurysm size was 8.6 mm. There were 44 unruptured IA and 5 ruptured IA. During endovascular treatment (EVT), adjunctive devices were used in 22.4% of procedures. A good clinical outcome (modified Rankin Scale score ≤2) was achieved in 44/48 patients (92%). There was no mortality. Mean follow-up was 25 months (range 3–72 months; median 24 months). Between mid term and long term follow-up, occlusion was stable in 19/23 IA (82.6%), improved in 2/23 IA (8.7%), and worsened in 2/23 IA (8.7%). Retreatment was performed in 8/49 IA (16.3%). At the latest available follow-up, there were 34/47 (72.3%) complete occlusions and 13/47 (27.7%) neck remnants. Conclusions: Our study suggests that EVT of IA with the WEB device provides adequate and stable long term occlusion.